Analisis Potensi Penerimaan Retribusi Jasa Usaha dan Kontribusinya terhadap Pendapatan Asli Daerah (PAD) di Kabupaten Lombok Barat - Nadiya Surya Rahmi; Siti Sriningsih; Ali Akbar Hidayat (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to determine the extent of business service retribution revenue in West Lombok Regency in 2019-2023 by analyzing the potential of business service retribution, then to determine the effectiveness of business service fees, and to determine the extent of the contribution of business service fees to local revenue (PAD) in West Lombok Regency from 2019 to 2023. This study uses quantitative research with a descriptive approach, utilizing data on target and actual business service fees and Local Original Revenue (PAD) data sourced from the Regional Revenue Agency (BAPPEDA) and dpjk.kemenkeu. Based on the research findings, the potential for business service fees at 158.6% falls into the category of low potential for Local Government Revenue (PAD) and meets the criteria for development. The growth rate of business service fees falls into the positive category with an average of 0.07%. The projected trend for the next three years falls into the negative category due to a declining trend. Based on the analysis of the effectiveness of business service fees in West Lombok Regency, it is categorized as less effective with an average of 62%. The contribution of business service fees is categorized as less contributing to Regional Original Revenue (PAD).